Analysis of The External Environment in The Face of TikTok Shop Closure - Faridi, Faridi; Kartono, Kartono (CV. Publikasi Indonesia, 2024)
Electronic Commerce or e-commerce is all buying and selling activities or transactions carried out using electronic media (the internet). Even though telephones and television are included as electronic means, e-commerce now refers more to digital technology or the internet. The purpose of researchers in conducting this analysis is to determine the threats and opportunities that will be faced by online shop MSMEs in Gegesik village, Cirebon Regency. This research uses a descriptive qualitative approach with a case study method. The research results from the closure of the TikTok Shop have an impact on the welfare of the people of Gegesik village who previously depended on the TikTok Shop and are now very confused. There are two camps of opinion, namely the first, there are those who agree that the TikTok Shop is closed. It is a threat to MSMEs in Indonesia because some think that the goods sold at the TikTok Shop are imported goods from China, Hong Kong, and Thailand, which will close down small companies. and medium and accompanied by a storm of mass layoffs and fear of user data being intercepted by other countries. The group that does not agree with TikTok Shop being closed believes that with social media like TikTok Shop, someone can once again struggle to earn a living to meet their family's needs, whereas those who were previously laid off (layoffs) can survive day after day because they rely on their hopes from TikTok Shop.